Anterior urethropexy according to lapides: how effective is it in the treatment of genuine female stress incontinence? - (:unkn) unknown (My University, 2003)
OBJECTIVES: Anterior urethropexy, introduced by Lapides, is a retropublic suspension procedure in which the anterior urethral wall is secured to the posterior surface of the symphysis pubis by full thickness trans-urethral sutures. Little information exists in the literature about its effectiveness and morbidity as a surgical treatment option for female stress incontinence. In this study, the outcome of this technique in the treatment of anatomic genuine stress urinary incontinence has been evaluated. METHODS: Thirty women with urodynamically-proven anatomic stress urinary incontinence underwent anterior urethropexy and 27 of them were followed up for a minimum of 12 months with a mean period of 28.9 months. RESULTS: A complete dry rate of 52% and a significant improvement of 11% were achieved at the mean follow up period. No postoperative retention or other significant complication was observed in the study group. De novo urge incontinence was noted in 2 patients and managed by anticholinergic treatment. CONCLUSION: Anterior urethropexy is found to be a safe retropubic suspension technique with a considerably low morbidity but revealed a relatively lower success rate compared other open bladder neck suspension techniques.
Keywords: Adult; Female; Humans; Middle Aged; Aged; Follow-Up Studies; Urologic Surgical Procedures; Urinary Incontinence, Stress